2015
DOI: 10.3233/nre-141201
|View full text |Cite
|
Sign up to set email alerts
|

Experienced usability of assistive technology for cognitive support with respect to user goals

Abstract: BACKGROUND: Studies have shown that Assistive Technology (AT) for cognitive support can support users in everyday activities. However, whether the AT actually supports the user to achieve their individual goals must further be examined. OBJECTIVE: The study objective was to examine the experienced usability of features in AT for cognitive support for users with cognitive impairment. METHODS: A content analysis was applied on data from interviews and field notes collected during two six-month interventions in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“… 19 , 28 , 38 , 40 , 43 , 47 , 49 , 51 Cavallo et al (2015) found that perceived usability could improve QoL for people with MCI/D and their FCs. 19 Cavallo et al (2015), 19 Leuty et al (2013), 47 and Lindqvist et al (2015) 43 used the same definition as this review regarding usability. Meiland et al (2012, p. 584) explained usability in terms of “user friendliness” (gratifying, easy to manage), “usefulness” (meeting the needs and desires of people with dementia), and “effectiveness” in promoting autonomy, coping, and QoL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 28 , 38 , 40 , 43 , 47 , 49 , 51 Cavallo et al (2015) found that perceived usability could improve QoL for people with MCI/D and their FCs. 19 Cavallo et al (2015), 19 Leuty et al (2013), 47 and Lindqvist et al (2015) 43 used the same definition as this review regarding usability. Meiland et al (2012, p. 584) explained usability in terms of “user friendliness” (gratifying, easy to manage), “usefulness” (meeting the needs and desires of people with dementia), and “effectiveness” in promoting autonomy, coping, and QoL.…”
Section: Resultsmentioning
confidence: 99%
“… 28 Lindqvist (2015, p. 138) operationalized the concept of usability to include three factors: the user’s desired goals, the hindering task according to the user, and the chosen assistive technology. 43 Some researchers used the term “user friendliness” instead of usability. 28 , 42 Boman et al (2014, p. 170) stated that acceptance of technology has been associated with “the ability to maintain a certain desired self-image of being competent.” 42 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, persons with cognitive impairment often need support from SOs in maintaining a smartphone [ 37 ]. It is well-known that the responsibility for supporting persons with cognitive impairment often lies with the SOs [ 38 ]. Caring for a person who has cognitive impairment can be a demanding task and can increase stress and decrease well-being for SOs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…By continuing to improve everyday technologies' original designs, an equitable use of everyday technology for people with diverse abilities can be promoted. Moreover, in order to make everyday technology enable functioning and everyday activity performance, aspects of usability and usefulness are very important to highlight in such design processes [6,8,32]. The result also indicates that generic competent everyday technology use cannot be taken for granted in any of the examined diagnostic subsamples (not even among older people without known cognitive impairments).…”
Section: Discussionmentioning
confidence: 99%
“…Usability, in turn, is a prerequisite for the technology's usefulness; i.e., how well it contributes to meeting the users' goals in specific activities [6]. The latter aspect, focusing on the individually determined relevance of a piece of technology, is particularly important in the context of rehabilitation and health care, where the goal is to base interventions on the clients' needs, yet usefulness has rarely been considered specifically in empirical research [8]. Similarly, although the concept ease-of-use is commonly accepted, less empirical knowledge exists on how easy or challenging people perceive those everyday technologies that are relevant in their lives to be.…”
Section: Introductionmentioning
confidence: 99%